Late Quaternary paleoenvironmental reconstructions from sediments of Lake Emanda (Verkhoyansk Mountains, East Siberia) - Andreev, Andrei A.; Nazarova, Larisa B.; Lenz, Marlene M.; Böhmer, Thomas; Syrykh, Ludmila; Wagner, Bernd; Melles, Martin; Pestryakova, Ludmila A.; Herzschuh, Ulrike; Nazarova, Larisa B.; 1 Alfred‐Wegener Institute, Helmholtz Centre for Polar and Marine Research Research Unit Potsdam Germany; Lenz, Marlene M.; 2 Institute of Geology and Mineralogy University of Cologne Germany; Böhmer, Thomas; 1 Alfred‐Wegener Institute, Helmholtz Centre for Polar and Marine Research Research Unit Potsdam Germany; et al. (Journal of Quaternary Science, 2022)
Continuous pollen and chironomid records from Lake Emanda (65°17′N, 135°45′E) provide new insights into the Late Quaternary environmental history of the Yana Highlands (Yakutia). Larch forest with shrubs (alders, pines, birches) dominated during the deposition of the lowermost sediments suggesting its Early Weichselian [Marine Isotope Stage (MIS) 5] age. Pollen‐ and chironomid‐based climate reconstructions suggest July temperatures (TJuly) slightly lower than modern. Gradually increasing amounts of herb pollen and cold stenotherm chironomid head capsules reflect cooler and drier environments, probably during the termination of MIS 5. TJuly dropped to 8 °C. Mostly treeless vegetation is reconstructed during MIS 3. Tundra and steppe communities dominated during MIS 2. Shrubs became common after ~14.5 ka bp but herb‐dominated habitats remained until the onset of the Holocene. Larch forests with shrub alder and dwarf birch dominated after the Holocene onset, ca. 11.7 ka bp. Decreasing amounts of shrub pollen during the Lateglacial are assigned to the Older Dryas and Younger Dryas with TJuly ~ 7.5 °C. TJuly increased up to 13 °C. Shrub stone pine was present after ~7.5 ka bp. The vegetation has been similar to modern since ca. 5.8 ka bp. Chironomid diversity and concentration in the sediments increased towards the present day, indicating the development of richer hydrobiological communities in response to the Holocene thermal maximum. Russian Scientific Foundation German Federal Ministry of Education and Research European Research Council http://dx.doi.org/10.13039/501100000781 Deutsche Forschungsgemeinschaft http://dx.doi.org/10.13039/501100001659 RSF Russian Ministry of Education and Science Federal Ministry of Education and Research BMBF